Ukraine - the forging of a nation - Hrycak, Jaroslav Josypovyč 1960- (PublicAffairs, 2024)
"When Russia invaded Ukraine in 2022, the world witnessed the creative, freewheeling, darkly humorous, and deeply resilient society that is contemporary Ukraine. In this timely and original history, a bestseller in Ukraine, the historian Yaroslav Hrytsak tells the sweeping story of his nation through a meticulous examination of the major events, conflicts, and developments that have shaped it over the course of centuries. Ukraine is essential reading for anyone who wants to better understand Ukraine's dramatic past and its global significance--from the 17th century Cossack uprising to the collapse of the USSR in 1991 and Ukrainian independence, and from the evolution of the Ukrainian language to the warning signs that anticipated Russia's 2022 invasion. This book is the definitive story of Ukraine and its people, as told by one of its most celebrated voices."--
This English translation originally published in Great Britain in 2023 by Sphere. - First published in Ukraine in 2022 by Portal Books under the title "Overcoming the past: Ukraine's global history
Keywords: Geschichte; Ukraine; Ukraine / History; Ukraine / Politics and government; Ukraine / Social conditions; Ukraine / Histoire; Ukraine / Politique et gouvernement; Ukraine / Conditions sociales; Nonfiction novels